Early warning value of multiple serum indicators combined with ultrasound detection in girls with central precocious puberty - Song, Xiaolong; Zhou, Jianping; Han, Tiantian; Lin, Zhifeng; Chen, Xu; Li, Yufang (Frontiers in Endocrinology, 2025)
AimThe aim of this study was to evaluate the early diagnostic potential of various serum biomarkers and ultrasound characteristics in girls diagnosed with early central precocious puberty (CPP).MethodsA cohort of 125 girls presenting breast development was assessed between May 2020 and January 2023. Following a six-month follow-up and GnRH agonist stimulation test, 78 girls were classified into the CPP group and 47 into the premature thelarche (PT) group. Serum biomarkers, including insulin-like growth factor-binding protein 3 (IGFBP-3), insulin-like growth factor 1 (IGF-1), and dehydroepiandrosterone sulfate (DHEAs), as well as bone age index (BAI) and ultrasound features, were compared between the groups.ResultsChronological age did not significantly differ between the groups, but bone age and BAI were notably higher in the CPP group. Most serum levels, except for peak FSH, were significantly elevated in the CPP group. Ultrasound metrics such as uterine volume, cervical ratio, ovarian volume, and milk bud characteristics also showed significant differences. Correlation analyses revealed positive associations between both physical and serum indices and peak LH levels. Receiver operating characteristic (ROC) curve analysis identified basal LH as having the highest area under the curve (AUC) of 0.927, followed by DHEAs (AUC = 0.924). Logistic regression identified LH and DHEAs as independent risk factors for CPP, with optimal diagnostic efficacy achieved when both markers were combined (AUC = 0.973).ConclusionBasal LH, IGF-1, IGFBP-3, DHEAs, and associated ultrasound features are valuable early indicators for CPP in girls. The combination of LH and DHEAs enhances diagnostic accuracy, establishing them as significant independent risk factors for CPP.